Application of Coastal Sediments and Foliar Seaweed Extract and Its Influence to Soil Properties, Growth and Yield of Shallot in Peatland - Sulakhudin, Sulakhudin; Hatta, Muhammad; Suryadi, Urai Edi (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2019)
The high soil acidity and low nutrient content in the peatland may inhibit the growth and yield of shallot and result low productivity. As consequence, the use of peat as a growing medium needs soil fertility improvement. One alternative to improve soil fertility, growth and yield of shallot is by applying coastal sediment and foliar seaweed extract which are easy to obtain and relatively inexpensive in West Kalimantan. This study aimed to investigate soil chemical properties, growth and yield of some shallot variety after the application of coastal sediment and foliar seaweed extract (Eucheuma cottonii). A field trial was carried out through the wet period of 2014 in West Kalimantan, Indonesia. The foliar seaweed extract was applied as the foliar fertilizer (0 and 3%), meanwhile the addition of coastal sediment was done at doses of 0 and 40 t/ha. The application of coastal sediment of 40 t/ha improved some chemical properties i.e. pH and the availability of K, Ca, Mg and Na of peat soil. The combination of foliar seaweed extract with 3% and 40 t/ha of coastal sediment increased growth and yield of all shallot variety in peatland compared to using foliar seaweed extract or coastal sediment only.